Charter 77 in the journalism of the Parisian “Kultura” - Fiktus, Paweł (Klio - Czasopismo Poświęcone Dziejom Polski i Powszechnym, 2021)
Although the Czechoslovak theme was not of particular interest in the journalism of “Kultura” (compared to Ukrainian or Lithuanian issues), it covered issues concerning Poland’s southern neighbour. The year 1968 marked a special period of increased interest in Czechoslovakia and the associated process of a series of social, political and economic reforms, which went down in history under the name of the Prague Spring. The period after the invasion by the Warsaw Pact troops and the start of the so-called process of normalization was also closely commented on by columnists and analysts of “Kultura”. However, particular attention was paid to the activities of the opposition in the area of Charter 77. The purpose of this article is to show how the Parisian “Kultura” referred to the opposition movement in Czechoslovakia. Moreover, Czechoslovak writers associated with Czechoslovak immigrant communities spoke out more often in “Kultura” pages